#### Answer

$d=\dfrac{L-a}{n-1} $

#### Work Step by Step

Subtract $a$ on both sides to find:
$L-a=(n-1)d$
Divide by $n-1$ on both sides to find:
$\dfrac{L-a}{n-1} = \dfrac{(n-1)d}{n-1}
\\\dfrac{L-a}{n-1} = d
\\d=\dfrac{L-a}{n-1}
$

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$d=\dfrac{L-a}{n-1} $

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.